2016
DOI: 10.1007/s00262-016-1823-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced local and systemic anti-melanoma CD8+ T cell responses after memory T cell-based adoptive immunotherapy in mice

Abstract: Adoptive cell transfer (ACT) melanoma immunotherapy typically employs acutely activated effector CD8+ T cells for their ability to rapidly recognize and clear antigen. We have previously observed that effector CD8+ T cells are highly susceptible to melanoma-induced suppression, whereas memory CD8+ T cells are not. Although memory T cells have been presumed to be potentially advantageous for ACT, the kinetics of local and systemic T cell responses after effector and memory ACT have not been compared. B16F10 mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Viral infections and tumor inoculations were performed per our previously published protocols [ 7 , 9 , 10 ]. In brief, Ly5.1+/C57BL/6 mice were infected with 2 × 10 5 PFU of Armstrong strain lymphocytic choriomeningitis virus (LCMV; gift from Marulasiddappa Suresh, University of Wisconsin) via intraperitoneal injection to generate CD8+ T cells specific for GP33, a class I MHC-restricted LCMV surface glycoprotein.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Viral infections and tumor inoculations were performed per our previously published protocols [ 7 , 9 , 10 ]. In brief, Ly5.1+/C57BL/6 mice were infected with 2 × 10 5 PFU of Armstrong strain lymphocytic choriomeningitis virus (LCMV; gift from Marulasiddappa Suresh, University of Wisconsin) via intraperitoneal injection to generate CD8+ T cells specific for GP33, a class I MHC-restricted LCMV surface glycoprotein.…”
Section: Methodsmentioning
confidence: 99%
“…Less-differentiated effector cells have been shown to have superior antitumor immunity compared to terminally-differentiated cells, potentially due to a number of mechanisms such as decreased IL-2 production and increased apoptosis with further differentiation [ 4 , 5 ]. Our laboratory and others have also demonstrated that ACT with T mem is more effective than ACT with T eff or naïve T cells [ 6 , 7 ]. T mem appear to be uniquely resistant to melanoma-induced suppression and generate a stronger intratumoral immune response [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of T cells from patients and the subsequent genetic modification of these cells with chimeric antigen receptors are under development as a promising alternative approach. Contreras et al [ 15 ] inoculated B16F10 melanoma cells that express very low levels of the lymphocytic choriomeningitis virus peptide GP33 (B16GP33) into syngeneic C57BL/6 mice. Subsequently, bona fide, naïve, effector, or memory phenotype GP33-specific CD8 + T cells were adoptively transferred into the mice after inoculation.…”
Section: Immunotherapy Approachesmentioning
confidence: 99%
“…Traditional ACT protocols exploit the antigen-specific cytolytic potential of CD8 + T cells by transferring terminally differentiated effector T (T EFF ) cells, but more recent evidence has shown that less differentiated cells, such as central memory T (T CM ) cells, show superior performance (14,15). Therefore, in this study, we used an immunotherapy platform that combines adoptive transfer of tumor-reactive T CM cells with oncolytic virus vaccines (OVVs).…”
Section: Introductionmentioning
confidence: 99%